Remley, Zita Donegan (audio interview #1 of 6) - Donegan Remley, Zita (11/4/1904 - 8/1/1985); Fischer, Jan, interviewer
INTERVIEW DESCRIPTION - This is the first of six separate interviews with Zita Remley conducted over a period of two years. This first interview was conducted as part of general course in oral history. 4/29/1976